Current time-motion analyses of professional football matches in top-level domestic leagues: a systematic review - Hands, D. E.; de Jonge, X. J. (International Journal of Performance Analysis in Sport, 2020)
This systematic review examined the literature on current time-motion analysis in national top-level association football leagues. Inclusion was limited to top division teams of national leagues, resulting in 20 studies reporting on Australia, England, France, Italy, Norway, Poland and Spain. Included studies used semi-automated camera tracking, global positioning systems and microwave radio frequency systems. Many variations of velocity thresholds and several definitions for high-speed activity (HSA) (>14.0 km·h-1; >14.1 km·h-1; >14.4 km·h-1) and very high-speed activity (VHSA) (>19.1 km·h-1; >19.8 km·h-1; >21.0 km·h-1) were reported. Average total distance (TD) ranged from 10,274 m (Australia) to 11,389 m (Italy). Comparison between positions showed that centre-backs generally covered the least distance (TD = 10,178 m; HSA = 1,886 m-1,940 m; VHSA = 391 m-621 m) and wide-midfielders the greatest distance (TD = 11,654 m; HSA = 3,006 m-3,406 m; VHSA = 753 m-1,216 m). This review of time-motion analysis demonstrated fairly similar outcomes for most domestic top-level leagues but suggests a strong influence of contextual variables. The consistently reported positional differences likely reflect the varied tactical demands of each position. The review proposes reaching a consensus on velocity threshold definitions and integrating contextual information in future research.